Trends in Hospital-to-Hospital Transfers for Aneurysmal Subarachnoid Hemorrhage: A Single Institution Experience From 2006–2017. (16th November 2020) - Adamczak, Stephanie; Patel, Devan; Fritz, Rachel; Polifka, Adam J; Hoh, Brian L; Fox, W. Christopher; Geh, Ndi
Abstract: INTRODUCTION: Aneurysmal subarachnoid hemorrhage (aSAH) is a life-threatening condition which requires emergent, expert medical care. METHODS: We performed a retrospective chart review of patients transferred to our high-volume center for aSAH between 2006 and 2017. Data collection included number of transfers, demographic data, Hunt Hess score, Fisher score, comorbid conditions, length of stay, discharge disposition, in-hospital mortality rates, insurance status, and hospital charges. Comparisons were made across three time periods (2006-2009, 2010–2013, and 2014–2017) and subgroup analyses by treatment modality (endovascular versus surgical clipping) were performed for all data. RESULTS: The number of transfers declined from 213 in 2006–2009 to 160 in 2014–2017. There is no difference in the proportion of endovascular treatment versus surgical clipping patients. There is no change in the presenting Hunt-Hess score of patients. The average Fisher score of all transfers increased significantly from 2.92 in 2006–2009 to 3.10 in 2014–2017 ( P < .001). Between 2006–2009 and 2014–2017, the average Charlson Comorbidity Index score increased from 1.80 to 2.64 ( P < .001) and the predicted 10-year survival decreased from 82.4% to 71.4% ( P < .001). Nonetheless, the average length of stay decreased from 26.2 days to 17.9 days ( P < .001). Overall home discharge rates did not change but subgroup analysis showed a marked decrease in the clipped cohort (42.5% in 2006–2009 versus 12.8% in 2014–2017; P = .0009). In-hospital mortality has decreased from 2006–2009 to 2014–2017, especially in the endovascular cohort (18.6% vs. 7.6%; P = .02). The proportions of patients who were either self-pay or had Medicaid did not change during the study period. After adjusting for inflation, overall hospital charges decreased from 76, 975 in 2006–2009 to 59, 870 in 2014–2017 ( P < .05). CONCLUSION: Patient transfers for aSAH are declining. These patients tend to have higher Fisher scores, more comorbid conditions, and lower predicted 10-year survivals, especially those who undergo surgical clipping. Despite these factors, the average length of stay, in-hospital mortality, and hospital charges are declining.